This is most easily proved by using the Kronecker totally anti-symmetric symbol "\\epsilon_{ijk}" such that "\\epsilon_{123}=0". Given two vectors "a" and "b" with the Cartesian components, respectively, "a_i" and "b_i", the Cartesian components of their vector product are given by
"\\left[ a \\times b \\right]_i = \\sum_{jk} \\epsilon_{ijk} a_j b_k \\, ,"and their scalar product is "a \\cdot b = \\sum_i a_i b_i". Applying these formulas, and using the simple relation "f \\nabla f = \\frac12 \\nabla f^2", we have
"\\nabla \\cdot \\left[ \\nabla f \\times \\left( f \\nabla g \\right) \\right] = \\nabla \\cdot \\left[ f \\nabla f \\times \\nabla g \\right] = \\frac12 \\nabla \\cdot \\left[ \\nabla f^2 \\times \\nabla g \\right] =""\\frac12 \\sum_i \\partial_i \\left[ \\nabla f^2 \\times \\nabla g \\right]_i = \\frac12 \\sum_{ijk} \\partial_i \\left( \\epsilon_{ijk} \\partial_j f^2 \\partial_k g \\right) =""\\frac12 \\sum_{ijk} \\epsilon_{ijk} \\left( \\partial_i \\partial_j f^2 \\partial_k g + \\partial_j f^2 \\partial_i \\partial_k g \\right) = 0 \\, ."The last equality is valid because "\\partial_i \\partial_j f^2" is symmetric with respect to {i, j}, and "\\partial_i \\partial_k g" is symmetric with respect to {i, k}, whereas "\\epsilon_{ijk}" is totally anti-symmetric.
Comments
Leave a comment